Hubungan Antara Efikasi Diri Dan Dukungan Orang Tua Dengan Motivasi Belajar Pada Siswa SMA - Tyas, Devi Marganing, Dra. Partini, M.Si (2016)
Learning motivation is necessary for the students as learners to achieve success or goal in the learning process. Self-efficacy and parental support is one of important factor that can affect the motivation of the student. This study was aimed to determine the relationship of self-efficacy and parental support toward the learning motivation of high school students; the relationship between self-efficacy toward the learning motivation of high school students; the relationship between parental support toward the learning motivation of high school students. Subjects in this study were 101 (M=42, F= 59) students of grade X in Klaten at the age of about 14-15 years old. The subjecs were taken by using a quota sampling technique. The methods of data collection was done by using learning motivation scale, self-efficacy scale and parental support scale. The technique of data analysis was done by using multiple regression analysis. Based on the analysis of this research, obtained result (a) There is a high significant relationship of self-efficacy and parental support toward the learning motivation (r= 0,705, p= 0,000); (b) There is a high significant positive relationship between self-efficacy and parental support (r= 0,676, p= 0,000); (c) There is a high significant positive relationship between parental support and learning motivation (r=0,472, p= 0,000); (d) Self-efficacy and parental support has coutributed to learning motivation with (R2= 0,457); Parental support has contributed to learning motivation with (R2= 0,223). Those three variable, learning motivation, self-efficacy and parental support have high categorization. The result of this research has implied the importance of self efficacy and parental support toward the learning motivation of students. The result will be discussed in this publication article.